Gibberellin Enhances the Anisotropy of Cell Expansion in the Growth Zone of the Maize Leaf - Sprangers, Katrien; Thys, Sofie; van Dusschoten, Dagmar; Beemster, Gerrit T. S. (Frontiers in Plant Science, 2020)
Although plant organ shapes are defined by spatio-temporal variations of directional tissue expansion, this is a little characterized aspect of organ growth regulation. Although it is well known that the plant hormone gibberellin increases the leaf length/with ratio, its effects on cell expansion in the growing leaf are largely unknown. To understand how variations in rate and anisotropy of growth establish the typical monocotelydonous leaf shape, we studied the leaf growth zone of maize (Zea mays) with a kinematic analysis of cell expansion in the three directions of growth: proximo-distal, medio-lateral and dorso-ventral. To determine the effect of gibberellin, we compared a gibberellin-deficient dwarf3 mutant and the overproducing UBI::GA20OX-1 line with their wild types. We found that, as expected, longitudinal growth was dominant throughout the growth zone. The highest degree of anisotropy occurred in the division zone, where relative growth rates in width and thickness were almost zero. Growth anisotropy was smaller in the elongation zone, due to higher lateral and dorso-ventral growth rates. Growth in all directions stopped at the same position. Gibberellin increased the size of the growth zone and the degree of growth anisotropy by stimulating longitudinal growth rates. Inversely, the duration of expansion was negatively affected, so that mature cell length was unaffected, while width and height of cells were reduced. Our study provides a detailed insight in the dynamics of growth anisotropy in the maize leaf and demonstrates that gibberellin specifically stimulates longitudinal growth rates throughout the growth zone.